Serum cystatin C and microalbuminuria in children with immune thrombocytopenia under short course of corticosteroids - Seham M. Ragab; Mohamed A. Helwa; Abdelfattah A. Khalaf (SpringerOpen, 2015)
Background: Corticosteroids are the universally accepted first line therapy for moderate and severe immune thrombocytopenia (ITP). Objectives: We investigated the effect of a short course prednisolone on serum cystatin C and the appearance of microalbuminuria as markers for renal injury in a group of ITP children. Methods: The study involved 33 (19 males, 14 females) newly diagnosed ITP children divided into two groups; group I included 15 children with no or mild bleeding treated according to "watch and wait" policy; group II included 18 children of moderate or severe bleeding treated by oral prednisolone. Fifteen healthy, age and sex matched children were enrolled as a control group. Blood urea, serum creatinine, estimated glomerular filtration rate (eGFR) by Schwartz formula, serum cystatin C (by ELISA) and urinary albumin concentration (by immunoturbidimetric assay) were determined. Results: The baseline investigations were comparable in the three groups and were within the reference ranges. Corticosteroids of 12 mg/kg cumulative dose had induced significant increments in serum creatinine [from 0.62 ± 0.16 to 0.84 ± 0.12 mg/dL, p < 0.0001] cystatin C [from 750.83 ± 108.1 to 2300.55 ± 991.94 ng/ml, p < 0.0001] and decreased eGFR [from 116.69 ± 40.87 to 79.76 ± 24.48 ml/min/1.73 m2, p = 0.001] without change in urinary albumin concentration or induction of microalbuminuria in paired analysis. Conclusion: Although not accompanied by microalbuminuria, steroid induced cystatin C elevation could be attributed in part to impaired GFR. Large population follow up studies are recommended to investigate the reversibility of this effect.